Proinflammatory cytokine IL-6 -174G/C (rs1800795) gene polymorphism among patients with chronic renal failure // Polimorfismo del gen de la citosina IL-6 pro inflamatoria en pacientes con insuficiencia renal crónica - Azeez, Sarhang H.; Darogha, Suhaila N. (Investigación Clínica, 2020)
Abstract Interleukin-6 polymorphism is regarded as an aggravating factor in the development and progression of renal disease. IL-6-174G/C (rs1800795) genotypes are associated with increased risk of cardiovascular events in patients receiving hemodialysis. The aim of this study was to determine the relation between IL-6 gene polymorphism in patients with chronic kidney disease, in an Iraqi Kurdish population. IL-6 polymorphism at -174G/C (rs1800795) was assessed in 108 patients with chronic kidney disease (54 on hemodialysis and 54 renal transplanted) and 54 healthy subjects. The mean ages were 46.1, 36.8, and 40.2 for the hemodialysis patients, renal transplanted and healthy subjects, respectively. In the hemodialysis patients, GC intermediate producers were found at a double-fold higher risk of progression of the disease. Allele frequency G was 0.66 and 0.74 for the patients and the control group, respectively. While for renal transplanted patients, GG high producers were lower than the control group. GC genotype was one-and-half-fold higher for the renal transplanted patients than the control group. Levels of serum IL-6 increased significantly in GG and GC genotypes between both patient groups (P<0.001). However, there was no significant difference between the patient and control groups in terms of their CC genotype (P>0.05). These findings support the hypothesis of the impact of IL-6 on the progression of chronic renal failure. The IL-6 -174G/C (rs1800795) polymorphism predicts the inflammatory status of the progressed disease, and has a significant effect on the level of pro-inflammatory cytokine IL-6 in end-stage renal disease patients. Resumen El polimorfismo de la interleucina-6 se considera un factor agravante en el desarrollo y la progresión de la enfermedad renal. Los genotipos de IL-6-174G / C se asocian con un mayor riesgo de eventos cardiovasculares en pacientes que reciben hemodiálisis. En este estudio se determinóla relación entre el polimorfismo del gen de la IL-6 y enfermedad renal crónica, en una población kurda iraquí. El polimorfismo de IL-6 a -174G/C se evaluó en 108 pacientes con enfermedad renal crónica (54 en hemodiálisis y 54 con trasplante renal) y en 54 sujetos sanos. En los pacientes en hemodiálisis, se encontró que los productores intermedios de GC tenían el doble de riesgo en la progresión de la enfermedad. La frecuencia alélica G fue de 0,66 y 0,74 para los pacientes y el grupo control, respectivamente. Mientras que, para los pacientes trasplantados renales, los productores con GG alto fueron menores que en el grupo de control. El genotipo de GC fue una vez y media más alto para los pacientes trasplantados renales que para los individuos sanos. El nivel de IL-6 sérica aumentó significativamente en los genotipos GG y GC entre ambos grupos de pacientes (P<0,001). Sin embargo, no hubo diferencias significativas entre los grupos de pacientes y de control en términos de su genotipo CC (P>0,05). Estos hallazgos apoyan la hipótesis del impacto de la IL-6 en la progresión de la insuficiencia renal crónica. El polimorfismo IL-6 (-174G/C) predice el estado inflamatorio de la enfermedad progresiva, y este polimorfismo tiene un efecto significativo en el nivel de la citoquina pro inflamatoria IL-6 en pacientes con enfermedad renal en etapa terminal.